Power games. (Economist, 2009)
The article reports that European energy companies have become increasingly powerful in the late 2000s. On February 20, 2009 Italian energy company Enel bought Spanish energy company Endesa. Other European energy companies such as E.ON, Vattenfall, and Nuon, have been involved in buyouts and buyout attempts as well.